Evaluation of polyester high-tenacity fabric and carbon nanotube reinforcements for improving flexural response in concrete beams - M. S. El-Feky; Amr H. Badawy; Khaled Mohamed Seddik; Sarah Yahia (Scientific Reports)
Abstract This research scrutinized the effectiveness of utilizing polyester high tenacity fabrics to enhance the functionality of concrete panels. Two distinct woven fabrics with comparable strength resistance were fabricated and assessed. Concrete beams were compared in their original form and those reinforced with woven fabrics, along with beams reinforced with carbon nanotubes (CNTs) (B, BC2, BC4, BS1, and BS2). Results indicated that the textile-reinforced concrete panels displayed notably greater energy absorption capabilities post-failure under flexural loads in comparison to the control and CNT-reinforced panels. This enhanced performance was credited to the development of multiple cracking patterns in the textile-reinforced panels. The flexural behavior of the textile-reinforced panels was characterized by four discernible phases: a linearly increasing segment, a crack propagation phase featuring multiple cracking, a post-cracking phase with reduced stiffness, and ultimately, failure due to fabric rupture or debonding. Conversely, the control and CNT-reinforced panels exhibited a more brittle response post-initial cracking, with a limited number of cracks and reduced deformation capacity. The performance of the textile samples was largely unaffected by their specific characteristics, except for the fabric wrapping angle. The introduction of 0.04% CNTs marginally enhanced crack flexural resistance compared to the control and 0.02% CNT panels, owing to the varied distribution of CNTs within the matrix. Overall, the textile-reinforced concrete panels demonstrated superior load-bearing capacity, ductility, and energy absorption when compared to the other reinforcement techniques examined.